Comparison of hybrid learning in Islamic education at middle school - Aida Hayani; Prasetya Aji, Bagus; Zulfikar Khabibulloh, Akhmad (UIN Salatiga, 2024)
After more than one year of education in Indonesia implementing learning in a waydaring it turns out that this has a negative impact on students. The purpose of this study is to compare online learning with offline learning (hybrid) at middle schools. The method used in this research is methodmix methods namely a method that combines quantitative research and qualitative research. The approach in this study uses the approach method sequential explanatory designs, where in the first stage the research is carried out using quantitative methods, namely searching for data which will then be analyzed using SWOT analysis and in the second stage it is carried out with qualitative methods using interview methods. The results of this study show the value of IFAS and EFAS in each lesson, namely 3.22, 2.68, 2.65 and 3.27. The results of qualitative research in this study show that in online learning students of class VIII SMP Mataram Kasihan show adaptations that are not appropriate or not optimal, this results in a decrease in the value of learning outcomes obtained by students. Whereas in offline learning the students of Mataram Kasihan Middle School showed a positive attitude in the form of enthusiasm, joy, joy, enthusiasm and like new motivation that had returned when offline learning had been carried out.